2020
DOI: 10.3390/pathogens9100798
|View full text |Cite
|
Sign up to set email alerts
|

A New Type of Chronic Wound Infection after Wisdom Tooth Extraction: A Diagnostic Approach with 16S-rRNA Gene Analysis, Next-Generation Sequencing, and Bioinformatics

Abstract: Delayed-onset infections are rare postoperative complications of lower third molar extractions. This article presents a case of a chronic combined hard and soft tissue infection after the extraction of a third molar, where the causative organisms could only be elucidated by molecular methods. Experimental 16S-rRNA gene analysis with next-generation sequencing and bioinformatics was used to identify the bacterial spectrum of the infection. 16S-rRNA gene analysis delivered the microbiome of the abscessing inflam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 39 publications
(76 reference statements)
0
7
0
Order By: Relevance
“…In this case, taking a swab can help distinguish classic mono-infections, which are often caused by easily culturable bacteria, from the typical anaerobic pathogen spectrum of odontogenic infections. In particular, infections with pyogenic Streptococci (e.g., peritonsillar abscess), abscesses caused by Staphylococci (especially S. aureus ), and infections with nonfermenting Gram-negative bacilli (NFGNB) [ 20 ] should be mentioned here, in which a possible adjuvant antibiotic therapy may need to be designed differently for the typical odontogenic abscess.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this case, taking a swab can help distinguish classic mono-infections, which are often caused by easily culturable bacteria, from the typical anaerobic pathogen spectrum of odontogenic infections. In particular, infections with pyogenic Streptococci (e.g., peritonsillar abscess), abscesses caused by Staphylococci (especially S. aureus ), and infections with nonfermenting Gram-negative bacilli (NFGNB) [ 20 ] should be mentioned here, in which a possible adjuvant antibiotic therapy may need to be designed differently for the typical odontogenic abscess.…”
Section: Discussionmentioning
confidence: 99%
“…Irrespective of the clinical therapy and culture results thereby obtained, the microbiome of the pus was determined from the frozen samples about three months later using 16S rRNA gene analysis [ 18 , 19 , 20 ]. 16S rRNA amplicon sequencing works like a bacterial fingerprint if the base sequence can be matched with a ribosomal database.…”
Section: Methodsmentioning
confidence: 99%
“…It is not always possible to sufficiently identify the causative pathogens by culture-based methods alone [ 10 ]—some authors even speak of culture-negative odontogenic abscesses if it is not possible to cultivate any pathogens at all [ 11 ]. Recent detection methods, not based on culturing, and particularly 16S rRNA gene analysis with subsequent gene sequencing, have shown that many bacteria of the oral cavity can only be determined with difficulty or even not at all by culture-based methods [ 3 , 12 , 13 ]. It has also not yet been possible to determine which bacteria of the oral and pharyngeal microbiome are exactly responsible for the acute inflammatory process and if the oral microbiome in these patients is composed differently compared to healthy people.…”
Section: Introductionmentioning
confidence: 99%
“…Since the introduction of the revolutionary method of bacterial characterization by Pace et al 26 , 16S rRNA-based characterization of bacterial species has been universally accepted as an accurate method for bacterial identi cation 27 . 16S rRNA metagenomic analysis has provided an objective tool to explore bacterial diversity and composition under a wide variety of clinical scenarios, in which 16S rRNA amplicon with SMS analysis was widely adopted for economic affordability and rapid microbial detection strategy 28 .To date, the use of 16S ribosomal RNA (rRNA) metagenomic analysis to study GM changes in the clinical setting have demonstrated the capability to analyze associations between GM changes and colorectal diseases 28 , COVID-19 infections 29 , prosthetic joint infections 30 , chronic wound infections after wisdom tooth extraction 31 , detection of postoperative infection sources 32 , and the potential to in uence SSI outcomes in colorectal surgery 14 . In this study, the 16S rRNA amplicon with SMS analysis was utilized to verify gut GM changes in mice.…”
Section: Discussionmentioning
confidence: 99%